Retrieval Algorithms for Road Surface Modelling Using Laser-Based Mobile Mapping - Jaakkola, Anttoni; Hyyppä, Juha; Hyyppä, Hannu; Kukko, Antero (Sensors (Basel, Switzerland), 2008)
Automated processing of the data provided by a laser-based mobile mapping system will be a necessity due to the huge amount of data produced. In the future, vehiclebased laser scanning, here called mobile mapping, should see considerable use for road environment modelling. Since the geometry of the scanning and point density is different from airborne laser scanning, new algorithms are needed for information extraction. In this paper, we propose automatic methods for classifying the road marking and kerbstone points and modelling the road surface as a triangulated irregular network. On the basis of experimental tests, the mean classification accuracies obtained using automatic method for lines, zebra crossings and kerbstones were 80.6%, 92.3% and 79.7%, respectively.